Gains in the Unit the Journey through the Turkish History in 7th Grade Social Studies Course and Gagne's Learning Outcomes - Cakmak, Zafer; Taskiran, Cengiz (Dergipark Akad, 2015)
In this study, the gains in the unit titled as the journey through the Turkish history taking place in the social studies 7th grade curriculum is aimed to be analyzed according to the learning outcomes of Gagne. The document analysis which is one of the qualitative researches has been used in this study. The social studies curriculum in use since 2004 and the Th grade social studies Teacher's book belonging to Anittepe Press being in the first place, the literature concerned has been benefited. Starting out with the data collected, presenting a descriptive table related to the research through comments is aimed. The 8 learning objective in the Journey through the Turkish History which appears in the social studies curriculum are analyzed one by one according to the Gagne's learning outcomes. In the result of the analyze, the outcomes are at the verbal information level. This indicates that the primary school general skills (critical, creative etc.) are not reflected efficiently.
Keywords: Robert Mills Gagne; Products of Learning; Social Science; Teaching of Social Studies